2008
DOI: 10.1371/journal.pone.0001647
|View full text |Cite
|
Sign up to set email alerts
|

Golgi Cisternal Unstacking Stimulates COPI Vesicle Budding and Protein Transport

Abstract: The Golgi apparatus in mammalian cells is composed of flattened cisternae that are densely packed to form stacks. We have used the Golgi stacking protein GRASP65 as a tool to modify the stacking state of Golgi cisternae. We established an assay to measure protein transport to the cell surface in post-mitotic cells in which the Golgi was unstacked. Cells with an unstacked Golgi showed a higher transport rate compared to cells with stacked Golgi membranes. Vesicle budding from unstacked cisternae in vitro was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 38 publications
7
86
0
3
Order By: Relevance
“…S8, rescue of the Golgi structure by GRASP65 expression reduced VSV-G trafficking at different time points of release. This result is consistent with our previous finding that disruption of Golgi enhances protein trafficking (14,15), in contract to the disruption of GM130 function, which slows trafficking (17).…”
Section: Grasp Expression Affects App Trafficking and Promotes α-Cleasupporting
confidence: 93%
See 2 more Smart Citations
“…S8, rescue of the Golgi structure by GRASP65 expression reduced VSV-G trafficking at different time points of release. This result is consistent with our previous finding that disruption of Golgi enhances protein trafficking (14,15), in contract to the disruption of GM130 function, which slows trafficking (17).…”
Section: Grasp Expression Affects App Trafficking and Promotes α-Cleasupporting
confidence: 93%
“…CIP is a 126-aa peptide containing p35 , which blocks cdk5 interaction with its activator p25, thereby specifically inhibiting cdk5. The CIP is fused to an 11-aa HIV TAT sequence (TAT-CIP) for better temporal and dosage control when applied to cells (14). TAT-GFP served as a control.…”
Section: Aβ Treatment Causes Golgi Fragmentation In Hippocampal Neuromentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Miller and co-workers have reported that CLASPdependent Golgi-derived microtubules are required for Golgi organization and polarized membrane trafficking (Miller et al, 2009). Furthermore, Wang and colleagues have reported that unstacking of the Golgi facilitates the post-Golgi transport of CD8 to the cell surface (Wang et al, 2008). Our results might support a possible mechanistic model in which Golgi-derived CLASP-dependent microtubules, which are regulated by GSK3 phosphorylation, control the organization of the Golgi and are involved in the sorting of cargo at the TGN.…”
Section: Gsk3 Is Involved In the Microtubule Dynamics Or Local Micromentioning
confidence: 99%
“…36,38 Unstacking exposes more surface area of the cisternae from which COPI vesicles can bud more efficiently and therefore contributes to the rapid disassembly of the Golgi during mitosis. 39 In telophase, the Golgi clusters merge and reform a new Golgi ribbon in each daughter cell. 40 …”
Section: Disassembly Of the Golgi During Mitosismentioning
confidence: 99%